2018
DOI: 10.22159/ajpcr.2017.v11i1.22558
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and in Vitro Antioxidant Activity of Whole Plant Extracts of Sesuvium Portulacastrum L

Abstract: Objectives: The objectives of this study are to screen the phytochemicals, estimate the content of phenolic and flavonoid compounds, and determine the antioxidant capacity of the Sesuvium portulacastrum L. (S. portulacastrum). Methods:The crude bioactives were extracted from the dried powder of S. portulacastrum in an orbital shaker using ethanol, methanol, acetone, hexane, and diethyl ether solvents. Rotaevaporator was used to concentrate the extracts. Total phenolic and flavonoid content was estimated spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
3
1
0
Order By: Relevance
“…Nayak et al (2018) reported presence of saponins, terpenoids, tannins, alkaloids and steroids in the methanol leaf extracts of Suaeda maritima, besides their presence in other mangroves such as Xylocarpus granatum, Avicennia marina, Salvador apersica and Avicennia o cinalis (Mulla and Chavan 2016). Similar to present study, ethanolic extract of Sesuviumportula castrum possesses phytochemicals like alkaloids, carbohydrates, cardiac glycosides, avonoids, phenols, saponins, sterols, terpenoids, quinones, diterpenes, and resins contributed to its therapeutic value (Chintalapani et al 2018).…”
Section: Discussionsupporting
confidence: 84%
“…Nayak et al (2018) reported presence of saponins, terpenoids, tannins, alkaloids and steroids in the methanol leaf extracts of Suaeda maritima, besides their presence in other mangroves such as Xylocarpus granatum, Avicennia marina, Salvador apersica and Avicennia o cinalis (Mulla and Chavan 2016). Similar to present study, ethanolic extract of Sesuviumportula castrum possesses phytochemicals like alkaloids, carbohydrates, cardiac glycosides, avonoids, phenols, saponins, sterols, terpenoids, quinones, diterpenes, and resins contributed to its therapeutic value (Chintalapani et al 2018).…”
Section: Discussionsupporting
confidence: 84%
“…The lack of fit F-value of 3.43 implies that the lack of fit is not significant relative to the pure error. This is in agreement with a study in which RSM was employed to optimize the conditions for antioxidant potential and polyphenols from apricot powder (Prunus armeniaca L.) using four independent variables: Methanol (20%, 35%, 50%, 65%, and 80%), solvent/sample ratio (10,15,20,25, and 30), temperature (20,30,40,50, and 60°C), and time (20,30,40,50, and 60 min). The results showed that antioxidant potential and total polyphenols in the experiments varied from 76.15% to 96.68% and 8.77 to 12.11 mg GAE/g, respectively.…”
Section: Statistical Analysis Of Datasupporting
confidence: 88%
“…It showed that combined formula antioxidant activity was better than single antioxidant and consistent with the regression model analysis [22]. In another study, the antioxidant activity of whole plant extracts of Sesuvium portulacastrum L. was checked by DPPH assay in which diethyl ether extract showed the highest total phenolic content and antioxidant potential among all the extracts of S. portulacastrum [15]. In the present study, the results of DPPH radical scavenging activity of ethanolic extract combination number 15 increased with increase in concentration representing a dose-dependent curve as shown in Figs scavenging activity on the DPPH radical which was found to be increasing with the increasing concentration and thus revealed dosedependent curves.…”
Section: Dpph Radical Scavenging Assaysupporting
confidence: 59%
“…Reactive oxygen species (ROS) and nitrogen (RNS) species act as pro-oxidants that either induces oxidative stress or inhibit the antioxidant activity and cause damage to proteins, lipid peroxidation, and fragmentation of deoxyribonucleic acid strand [3]. The process ultimately leads to cellular injury, aging, cancer, and hepatic, neurodegenerative, cardiovascular, and renal disorders [4,5].…”
Section: Introductionmentioning
confidence: 99%